PERAN PERKEMBANGAN KEGIATAN INDUSTRI DAN PERDAGANGAN JASA TERHADAP PERUBAHAN STRUKTUR RUANG KAWASAN SOLO BARU - Intan Dwi Astuti; Murtanti Jani Rahayu; Rizon Pamardhi Utomo (ARSITEKTURA, 2015)
Solo Baru area is a satellite city that grew due to the phenomenon of urban sprawl in Surakarta. This area growth of more advanced and dominated by economic activity, especially industrial and trade-services activities.  The problem is development on industrial and trade-services activities  occur   in Solo Baru certainly will encourage a change in the spatial area as centers of activities, patterns of land use and road network. Changes in the spatial aspect will have a negative impact on the regularity of the spatial structure and function of  the area to the surrounding area. Therefore, this research was conducted to determine the role of the development of industrial and trade-services activities to the changes in the spatial structure of Solo Baru area . The method of research is deductive-quantitative, while the data analisys technique used is  descriptive analysis of quantitative and spatial descriptive. The results of this study notes that both of industrial and trade-services activities have developed from years 2002-2014 that occurred development of industrial activity by 43% and trade-services activities amounted to 140%.  The role of the development of industrial and trade-services activities include the agglomeration of activities and to encourage a change in the distribution centers that changes occur in the central-subcentral models that undergo a change from a non-centered to form multi-nodal. In addition, the  industrial and trade-services activities also encourage land use changes and then give impact to the shift and functional zoning exist within the area as well as attract more movement leads to a change in the function and capacity of the road network. Keywords: activity development role, industrial, spatial structure, trade-services